2022
DOI: 10.1186/s12951-022-01409-6
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable nano-pesticide platform based on Pyrethrins II for prevention and control Monochamus alternatus

Abstract: Background Pine wilt disease as a devastating forest disaster result from Bursaphelenchus xylophilus that spread by stem-borers Monochamus alternatus feeding on pine leaves, which has brought inestimable economic losses to the world's forestry due to lack of effective prevention and control measures. In this paper, we put forward a proposal for utilizing nanoHKUST-1 to encapusulate the Pyrethrins II that a nerve agent extracted from plant to control M. alternatus, including toxicity mechanism r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…This can reduce the environmental pollution caused by one-time release and achieve the long-term effective control of the target pest. 32…”
Section: Resultsmentioning
confidence: 99%
“…This can reduce the environmental pollution caused by one-time release and achieve the long-term effective control of the target pest. 32…”
Section: Resultsmentioning
confidence: 99%
“…Recently, nanomaterial-based pesticide delivery systems (PDSs) have drawn increasing interest for their controllable preparation route, improved water dispersion stability, high pesticide loading rate, sustained release, and enhanced insecticidal activity. Materials including carbon nanomaterials, polymers, metal–organic frameworks, mesoporous materials, etc., are developed as nanocarriers for pesticide delivery in the past decade. , Especially, the stimuli-responsive controlled release of PDSs has attracted extensive interest because the pesticide release behavior can be accurately controlled according to exogenous stimuli, which will greatly improve the utilization and activity of pesticides. For example, Kaziem et al developed a carboxymethyl starch-modified hollow mesoporous silica-based PDS for abamectin delivery and found that the release of abamectin can be controlled by pH and enzyme dual stimuli . Song and colleagues reported a carboxymethyl chitosan surface-decorated carbon nanoparticle for emamectin benzoate (EB) delivery and found that it exhibited pH-responsive release performance .…”
Section: Introductionmentioning
confidence: 99%
“…7−10 Materials including carbon nanomaterials, polymers, metal−organic frameworks, mesoporous materials, etc., are developed as nanocarriers for pesticide delivery in the past decade. 11,12 Especially, the stimuliresponsive controlled release of PDSs has attracted extensive interest because the pesticide release behavior can be accurately controlled according to exogenous stimuli, which will greatly improve the utilization and activity of pesti-cides. 13−17 For example, Kaziem et al developed a carboxymethyl starch-modified hollow mesoporous silicabased PDS for abamectin delivery and found that the release of abamectin can be controlled by pH and enzyme dual stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…Pine wilt disease can infect more than 50 kinds of pine trees, which has brought direct economic losses and ecological service value losses of more than 10 billion CNY per year in China 1 . Effective prevention and control of Monochamus alternatus Hope has become a key factor to cut off the transmission of this pine cancer 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Pine wilt disease can infect more than 50 kinds of pine trees, which has brought direct economic losses and ecological service value losses of more than 10 billion CNY per year in China. 1 Effective prevention and control of Monochamus alternatus Hope has become a key factor to cut off the transmission of this pine cancer. 2 The chemical control method of spraying pesticides and the biological control technique of releasing natural enemy are widely used to kill larval and adult cerambycids in May to August.…”
Section: Introductionmentioning
confidence: 99%